The knowledge concerning the balanced development among the high school students based on the initial research - Żeber-Dzikowska, Ilona (Studia Ecologiae et Bioethicae, 2008)
The balanced development is at present the challenge for creating the awareness not only of the particular society, but also in the widest sense for the whole generation of the people. Undertaking such issues, the role of education during all stages of teaching, should be taken into consideration, especially, in the range of propagating the idea of responsibility for the natural environment with eco-development. It is a specially important element of teaching according to the principle of pro-environmental education to undertake all actions in the educational centers, which aim is to stimulate the environmental awareness of young people as well as to prepare the pedagogical staff to the realization of the wide range of methods and strategies that allow to get the best results during the process of educating young generation. The appropriate undertakings should be realized in order to support the education in the process of introducing the right value system and positive attitudes towards realization of the sixth Environmental politics of the EU Programme. With the connection to the carried on initial research associated with the knowledge about the balanced development among high school students, analysing the results of the questionnaires, the answer to the question whether students possess any kind of knowledge on balanced development was to be learned.